Classification of derivation algebras in low dimensions - Guediri, Mohammed; Albalawi, Kholoud (King Saud University, 2018)
A left-symmetric algebra A is said to be a derivation algebra if all its left and right multiplications are derivations of the Lie algebra associated to A. In this paper, we shall study derivation algebras over R and then classify almost all those of dimensions ≤ 4
Keywords: Extensions of left-symmetric algebras; Left-invariant afﬁne connection; Novikov algebras; Derivation algebras